PERSEPSI MAHASISWA MAGISTER PAI TERHADAP PROGRAM FIELD STUDY DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK - Mohammad Ilham Al Ghifary; Musthofa Musthofa; Ahmad Arifi (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Abstract, The importance of the role of teachers and lecturers in the field of Education encourages the government to organize specialized education for individuals who aspire to become teachers or lecturers. In this case, it is taught at the higher education level in institutions that have faculties of Education and Pedagogy. Students pursuing a degree in the field of education are called education students, who are considered as potential successors to the struggles of teachers and lecturers. In this case, it is taught at the higher education level in institutions that have faculties of Education and Pedagogy. Students pursuing a degree in the field of education are called education students, who are considered as potential successors to the struggles of teachers and lecturers. This research aims to explore the perceptions of Master of Islamic Education (PAI) students towards the Field Study program in enhancing pedagogical competence and the importance of implementing this program. The research method used in this study is descriptive qualitative, and the research subjects were selected using purposive sampling technique, which is an approach taken by the researcher to determine the informants. Data collection techniques include observation, interviews, and documentation. The data analysis employs the interactive model by Miles and Huberman, which involves data collection, data reduction, data display, and drawing conclusions. The research findings reveal that fundamentally, the Field Study program has a clear purpose and objective, which is to provide preparation for Master's students in the Faculty of Islamic Education and Pedagogy to become competent educators through research, community engagement, and teaching practice. It is through teaching practice that students have the opportunity to enhance their pedagogical competence as prospective educators.